Perbandingan Efektivitas Diazepam dan Magnesium Sulfat dalam Penanganan Kejang pada Tetanus: Tinjauan Literatur - Iwan Setiawan Adji; Lina Nur Fatimah; Dhia Laila Nadzifa; Witrishya Anggrahini; Noval Gentha Mahensa (Yayasan Literasi Sains Indonesia, 2025)
Seizures are a serious complication of tetanus, contributing to high morbidity and mortality rates. Various therapeutic approaches have been employed to manage seizures, including diazepam and magnesium sulfate. This literature review aims to compare the effectiveness of these two agents in reducing both the frequency and severity of seizures in tetanus patients. A systematic search was conducted using scientific publications from PubMed, Google Scholar, and ScienceDirect over the past ten years. The review indicates that magnesium sulfate shows potential as an effective and relatively safe alternative to diazepam in certain clinical settings. However, variations in study design and limited available data highlight the need for further clinical trials to strengthen existing evidence. This review is expected to serve as a reference for clinicians in selecting optimal anticonvulsant therapy for tetanus cases. Furthermore, the study emphasizes the importance of understanding the pharmacological mechanisms, clinical indications, and monitoring of adverse effects to ensure both safety and efficacy of the therapy. Overall, this literature review contributes to the development of evidence-based clinical guidelines for managing seizures in tetanus patients.